2010
DOI: 10.1002/sia.3601
|View full text |Cite
|
Sign up to set email alerts
|

XPS study on band alignment at PtO‐terminated ZnO(0001) interface

Abstract: The band alignment at the interface between Pt and O-terminated ZnO(0001) was investigated by depositing Pt films on ZnO using X-ray photoelectron spectroscopy and ultra violet photoelectron spectroscopy in an ultrahigh vacuum system. Angle-resolved X-ray photoelectron spectroscopy measurement showed the band was bent down by 0.06 eV at the ZnO(0001) surface. The binding energy of Zn 2p doublet shifted toward higher values by 0.37 eV when Pt was deposited on ZnO(0001). The work function of ZnO(0001) was 4.08 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 11 publications
5
12
0
Order By: Relevance
“…The E VBM (2.8–3.3 eV) and Φ (4.1 eV) values found for the sample without water after H* treatment agree very well with published values by Kim et al [35] ( Φ  = 4.08 eV) after Ar + ion sputtering/heating ZnO single crystal at 700 °C, Gutmann et al [19] ( E VBM  = 3.0 eV, Φ  = 4.1 eV) on nanocrystalline ZnO surfaces after annealing at 400 °C in UHV environment, and Heinhold et al [21] ( E VBM  = 3.41 eV) after annealing ZnO single crystal at 750 °C for 15 min. This agreement is not surprising since annealing or Ar + ion sputtering has similar effect of partial cleaning of ZnO as H* treatment.…”
Section: Resultssupporting
confidence: 90%
“…The E VBM (2.8–3.3 eV) and Φ (4.1 eV) values found for the sample without water after H* treatment agree very well with published values by Kim et al [35] ( Φ  = 4.08 eV) after Ar + ion sputtering/heating ZnO single crystal at 700 °C, Gutmann et al [19] ( E VBM  = 3.0 eV, Φ  = 4.1 eV) on nanocrystalline ZnO surfaces after annealing at 400 °C in UHV environment, and Heinhold et al [21] ( E VBM  = 3.41 eV) after annealing ZnO single crystal at 750 °C for 15 min. This agreement is not surprising since annealing or Ar + ion sputtering has similar effect of partial cleaning of ZnO as H* treatment.…”
Section: Resultssupporting
confidence: 90%
“…These experiments yielded values between 4.45 eV and 4.50 eV. 24 The work function value found for the annealed surface (4.1 eV) agrees well with a published value by Kim et al 25 They measured a UPS derived work function of 4.08 eV on an Ar þ ion sputtered/heat treated (700 C) ZnO single crystal surface.…”
Section: Discussionsupporting
confidence: 75%
“…Continuity between coating and substrate indicated strong bonding force by MAO, and the Ag and Zn contents increased gradually from the substrate to the coating surface (Figure 13d). Ag was composed of 73% Ag 2 O and 27% metallic Ag [103,104], while Zn existed in the form of ZnO [105]. TEM images indicated that many large rutile or anatase grains of 20-40 nm in size (Figure 13e,f) and many relatively small Ag nano-grains with sizes of 5-10 nm (Figure 13f) were homogenously embedded in amorphous TiO 2 matrix.…”
Section: Introduction Of Both Metal Nanoparticles and Metallic Compoumentioning
confidence: 99%